2021
DOI: 10.1002/1878-0261.13057
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses of high‐grade neuroendocrine gynecological malignancies reveal a unique mutational landscape and therapeutic vulnerabilities

Abstract: List of abbreviations: BWA: Burrows-Wheeler alignment CNV: Copy number variation COMPASS: Complex proteins associated with Set1 DDR: DNA damage response FDR: False discovery rate FFPE: Formalin-fixed paraffin-embedded FIGO: International federation of gynecology and obstetrics (Fédération Internationale de Gynécologie et d'Obstétrique, French) HPV: Human papilloma virus IHC: Immunohistochemistry lincRNA: Long intergenic non-coding RNA MAF: Mutation annotation format NEC-GYN: Neuroendocrine carcinoma of gynecol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Nevertheless, their part in treating gynecologic tract NENs is limited due to low incidence or insufficient clinical trials data. A comprehensive study by Mahdi et al reported that gynecological NEC demonstrated frequent mutations in KMT2C and KMT2D genes involved in gene enhancers regulation [ 113 ]. They also found that DDR (DNA damage response) gene mutations are high in gynecological NEC, making them susceptible to PARP inhibitors.…”
Section: Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, their part in treating gynecologic tract NENs is limited due to low incidence or insufficient clinical trials data. A comprehensive study by Mahdi et al reported that gynecological NEC demonstrated frequent mutations in KMT2C and KMT2D genes involved in gene enhancers regulation [ 113 ]. They also found that DDR (DNA damage response) gene mutations are high in gynecological NEC, making them susceptible to PARP inhibitors.…”
Section: Future Perspectivementioning
confidence: 99%
“…They also found that DDR (DNA damage response) gene mutations are high in gynecological NEC, making them susceptible to PARP inhibitors. In addition, mutations in CCDC6 suggest promising benefits from PARP inhibitors [ 113 ]. Further studies are required to evaluate the efficacy of targeted immunotherapy against HMGB1/TIM-3 and CD47/SIRPα.…”
Section: Future Perspectivementioning
confidence: 99%
“…Microphthalmia-associated transcription factor (MITF/MiT) family translocation renal cell carcinoma and other types of tumors, such as perivascular epithelioid cell neoplasm and alveolar soft part sarcoma, are known to harbor MALAT1 fusion with TFE3 , TFEB , TFEC , and MITF . MALAT1 fusions, including MALAT1::SMG , EEF1A1::MALAT1 , and ASH1L::YY1AP1 , have been detected in nearly 20% of all fusion gene events in gynecologic high-grade neuroendocrine carcinomas [ 34 ]. Together with the results presented in this study, these findings suggest that MALAT1 can be highly available for gene rearrangement to form oncogenic fusions; however, the biological and clinical significance of these MALAT1 fusions has not been fully investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, in a series of forty pathologic specimens from patients with NECs of the cervix, PD-L1 was positive (considered as a composite proportion score ≥ 1) in only 8% of samples, while all were microsatellite-stable by IHC [92]. However, mutations in DNA damage response (DDR) genes, which can be commonly observed in GY-NECs, also induce the accumulation of DNA mutations, which cause high TMB [93], which is a predictive factor of the activity of ICIs in several malignancies [94,95]. Indeed, a cohort of the DART SWOG 1609 phase II study investigated the activity of the combination of ipilimumab and nivolumab in non-pancreatic neuroendocrine neoplasms [96].…”
Section: Necs Of the Cervixmentioning
confidence: 99%